Perempuan dalam Melaksanakan Mandat Ilahi Menurut Kejadian 1:27-28 - Sarah Wassar (REDOMINATE: Jurnal Teologi dan Pendidikan Kristiani, 2022)
God gave a divine mandate to humans (women and men) since the beginning of creation is to rule the world (Genesis 1:27). Women and men were created in the image and likeness of God, equal in God's presence, and received the same Divine mandate and carried out the Divine mandate according to God's commands or will. To find out specifically about women in carrying out Divine mandates, this writing is reviewed theologically using qualitative methods, namely literature or literature study. Then it is presented in the form of a theological review description. AbstrakAllah memberikan mandat Ilahi kepada manusia (perempuan dan laki-laki) sejak awal penciptaan adalah menguasai dunia (Kej. 1:27). Perempuan dan laki-laki diciptakan menurut gambar dan rupa Allah, setara dalam hadirat Allah, menerima mandat Ilahi yang sama dan melaksanakan mandat Ilahi sesuai dengan perintah atau kehendak Allah. Untuk mengetahui secara khusus tentang perempuan dalam melaksanakan mandat Ilahi, maka penulisan ini ditinjau secara teologis dengan menggunakan metode kualitatif yaitu literatur atau studi pustaka. Kemudian disajikan dalam bentuk diskripsi tinjauan telogis.